Whole food, functional food, and supplement sources of omega-3 fatty acids and omega-3 HUFA scores among U.S. soldiers. (May 2016) - Hanson, Jennifer A.; Lin, Yu-Hong; Dretsch, Michael N.; Strandjord, Sarah E.; Haub, Mark D.; Hibbeln, Joseph R.
Highlights: Dietary intake and omega-3 biomarkers were measured in a sample of U.S. soldiers. Eighteen percent of participants consumed at least one omega-3 functional food. Thirteen percent of participants had taken an omega-3 supplement. Supplements and functional foods were associated with higher biomarkers. Smoking and beef intake were associated with lower biomarkers. Abstract: A questionnaire to measure consumption of contemporary sources of omega-3 fatty acids including (i) seafood, (ii) poultry and eggs, (iii) omega-3 functional foods, and (iv) dietary supplements was completed by U.S. soldiers (N = 191). Omega-3 highly unsaturated fatty acid (HUFA) scores were higher (p < 0.01) among those who (i) took an omega-3 supplement, (ii) consumed sushi, (iii) consumed omega-3 functional foods, (iv) consumed beef less than twice per week, and (v) ate seafood at least twice a week. Omega-3 HUFA was positively correlated with EPA + DHA intake (β = 0.39; p < 0.01) and age (β = 0.14; p = 0.03) and negatively correlated with beef intake (β = −0.13; p = 0.05) and smoking (β = −0.12; p = 0.08). Intake of contemporary foods rich in omega-3s were associated with higher biomarker values while smoking and beef intake were associated with lower values.